2012
DOI: 10.1021/cs300224j
|View full text |Cite
|
Sign up to set email alerts
|

Controllable Synthesis and Acetylene Hydrogenation Performance of Supported Pd Nanowire and Cuboctahedron Catalysts

Abstract: Supported Pd nanowire and cuboctahedron catalysts have been synthesized in an ethylene glycol− poly(vinylpyrrolidone)−KBr system using a precipitation− reduction method. KBr plays a critical role in controlling the morphology of Pd: with a variety of relatively low KBr concentrations, Pd nanowires with different lengths were obtained, but after adding sufficient KBr, shape evolution from nanowires to cuboctahedrons was observed. HRTEM images showed that the twisted Pd nanowires were actually composed of primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 61 publications
3
49
0
1
Order By: Relevance
“…Evidently, no extra diffraction peaks of carbon can be found in C-mb-TiO 2 , which implies that either the amount of carbon is too little or the generated carbon is amorphous [21]. In addition, the diffraction peaks for Pd are indistinguishable, which may be caused by the low content or good dispersion, as previously reported [22]. The bicrystalline structure was also confirmed by Raman spectra.…”
Section: Introductionsupporting
confidence: 77%
“…Evidently, no extra diffraction peaks of carbon can be found in C-mb-TiO 2 , which implies that either the amount of carbon is too little or the generated carbon is amorphous [21]. In addition, the diffraction peaks for Pd are indistinguishable, which may be caused by the low content or good dispersion, as previously reported [22]. The bicrystalline structure was also confirmed by Raman spectra.…”
Section: Introductionsupporting
confidence: 77%
“…This was attributed to the influence of hydride formation/decomposition (hydride decomposition occurred at lower temperature on nanocubes) and weaker ethylene adsorption on (100) faces [31]. He et al [32] explored the differences of Pd cuboctahedron and nanowires towards acetylene hydrogenation prepared by varying the amount of bromide added to the synthesis procedure. High resolution TEM images indicated that nanowires were composed of smaller cuboctahedra connected by different crystal faces.…”
Section: Figmentioning
confidence: 99%
“…Testing under competitive conditions demonstrated that nanowires were more active than the cuboctahedra although not as selective. The enhanced activity of the nanowires was attributed to a larger number of defect sites associated with the wire being composed of a number of smaller interconnecting cuboctahedra [32].…”
Section: Figmentioning
confidence: 99%
“…In the selective hydrogenation of acetylene, Li et al [31] reported that the hydrogenation activity of the Pd nanowires increased because of the defect sites at crystal boundaries. In our previous work [32], a larger amount of Ti 3+ surface defects on the solvothermal-derived nanocrystalline TiO 2 was also found to result in a stronger interaction between Co and TiO 2 and then a higher Co dispersion.…”
Section: Selective Hydrogenation Of Acetylenementioning
confidence: 99%